Notes on Twentieth-Century German Public Opinion, Colonialism, and the Portuguese Colonies (a Tentative Approach) - Clara,Fernando (2019)
German attitudes towards colonialism have been the object of several recent studies that are primarily interested in the internal dynamics of German colonial history. Only a few of these studies, however, direct some attention to international colonial settings and, not surprisingly, the number of those addressing the Portuguese colonies is quite small. This paper explores the political and, above all, the cultural framework under which the discussions on Portuguese colonialism take place in twentieth-century Germany. It highlights the continuities underlying the complex German-Portuguese colonial networks before and after World War II and focuses mainly on their genealogical paths, historical motivations, and intellectual as well as political backgrounds. On the whole, these notes are meant to contribute to a more contextualised and differentiated understanding of German public opinions sensitivity to colonialism, and especially to the Portuguese colonial regime during the period.